IMPLEMENTASI MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS III SD - Amalia, Risa; Falah, Irfan Fajrul (Universitas Negeri Medan, 2025)
The purpose of this study was to compare the learning motivation of students who used graphic learning media and those who used word walls. In addition, the purpose of this study was to determine whether or not there were significant differences between the two types of educational media. A quantitative experiment was conducted for the purpose of this study on students from Pajawankidul Elementary School enrolled in grade III A. The experimental class consisted of students from grade III A, while the second experimental class consisted of students from grade III B. When conducting the sampling method, a number of different types of media, such as word walls and photos, were used. The sample included a total of twenty male students and twenty-eight female students. The total number of students participating in the sample was twenty. Students in grades III A and III B who were studying science showed various learning interests when they were exposed to word walls and image learning media on their computers, according to the conclusions of the study presented. Third-grade students of Pajawankidul Elementary School had better learning motivation when they utilized word walls as one type of media compared to visual media.